2017
DOI: 10.4172/2167-1222.1000370
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Delayed Union of Long Bones

Abstract: Aim: To study the epidemiology of delayed union of long bones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…25 26,27 In this series nailing resulted in better union rates. Delayed union was noted up to 18.5% in Fong et al and 18.95% in Mehmood et al 28,29 Factors which influenced delayed union in this review was grade of injury. In a study by Westgeest et al with a study of 736 subjects concluded that higher Gustilo grade fractures were associated with non-union and delayed union.…”
Section: Discussionmentioning
confidence: 60%
“…25 26,27 In this series nailing resulted in better union rates. Delayed union was noted up to 18.5% in Fong et al and 18.95% in Mehmood et al 28,29 Factors which influenced delayed union in this review was grade of injury. In a study by Westgeest et al with a study of 736 subjects concluded that higher Gustilo grade fractures were associated with non-union and delayed union.…”
Section: Discussionmentioning
confidence: 60%
“…Large bone defects are difficult to manage and can result in nonunions (Gomez‐Barrena et al, 2015; Mehmood, Deshpande, Khan, Singh, & Patil, 2017). In this case, the bone defect resulted from the removal of abnormal and infected bone that occurred after trauma.…”
Section: Discussionmentioning
confidence: 99%
“…16.7% of the patients in this study had delayed union, which is comparable to Katie fong, et al [39] . Who had 18.5% and Moin Mehmood et al [40] . Had 18.95%.…”
Section: Factors Influencing Unionmentioning
confidence: 98%